Development of the Korean Medicine Core Outcome Set for Stroke Sequelae: Herbal Medicine Treatment of Elderly Patients With Stroke Sequelae in Primary Clinics - Cha, Jiyun; Kim, Sungha; Kim, Pyung-Wha; Lee, Hesol; Ko, Mi Mi; Jang, Soobin; Lee, Myeong Soo (Frontiers in Pharmacology, 2022)
Objectives We developed a Korean medicine core outcome set for stroke sequelae (COS-SS-KM) to evaluate the effectiveness and safety of herbal medicine for stroke sequelae, especially for elderly stroke patients in primary clinics. Methods Researchers identified previously reported outcomes from a literature review and defined the list of outcomes and effect modifiers for the core outcome set (COS) questionnaire. Three rounds of modified Delphi consensus exercises with experts were conducted online for suitability assessment, and one round of a modified Delphi consensus exercise with primary clinicians was conducted for feasibility assessment. Results The review identified 17 outcomes and 16 effect modifiers; moreover, six outcomes and one effect modifier were suggested by the experts. The final COS comprised 8 outcomes and 12 effect modifiers for history taking, and experts listed 13 major symptoms of stroke sequelae for symptom assessment. The clinicians agreed on the feasibility of the COS. Conclusion This COS will help primary care researchers assess the effectiveness of pharmacotherapy, including herbal medicine, for elderly patients with stroke sequelae. Future studies should focus on reflecting the opinions of all stakeholders.